De Novo Genome Assembly and Comparative Genomics of the Barley Leaf Rust Pathogen Puccinia hordei Identifies Candidates for Three Avirulence Genes. Issue 10 (1st October 2019) - Chen, Jiapeng; Wu, Jingqin; Zhang, Peng; Dong, Chongmei; Upadhyaya, Narayana M; Zhou, Qian; Dodds, Peter; Park, Robert F
Abstract: Puccinia hordei ( Ph ) is a damaging pathogen of barley throughout the world. Despite its importance, almost nothing is known about the genomics of this pathogen, and a reference genome is lacking. In this study, the first reference genome was assembled for an Australian isolate of Ph (" Ph 560") using long-read SMRT sequencing. A total of 838 contigs were assembled, with a total size of 207 Mbp. This included both haplotype collapsed and separated regions, consistent with an estimated haploid genome size of about 150Mbp. An annotation pipeline that combined RNA-Seq of Ph -infected host tissues and homology to proteins from four other Puccinia species predicted 25, 543 gene models of which 1, 450 genes were classified as encoding secreted proteins based on the prediction of a signal peptide and no transmembrane domain. Genome resequencing using short-read technology was conducted for four additional Australian strains, Ph 612, Ph 626, Ph 608 and Ph 584, which are considered to be simple mutational derivatives of Ph 560 with added virulence to one or two of three barley leaf rust resistance genes ( viz. Rph3, Rph13 and Rph19 ). To identify candidate genes for the corresponding avirulence genes AvrRph3, AvrRph13 and AvrRph19, genetic variation in predicted secreted protein genes between the strains was correlated to the virulence profiles of each, identifying 35, 29 and 46 candidates for AvrRph13, AvrRph3 and AvrRph19, respectively. The identification of these candidate genes provides a strong foundation for future efforts to isolate these three avirulence genes, investigate their biological properties, and develop new diagnostic tests for monitoring pathogen virulence.